Theoretical Study of Fretting Wear Rate Evolution in Axi-Symmetrical Elastic Contact Using the Method of Dimensionality Reduction - Dimaki, Andrey V. (Frontiers in Mechanical Engineering, 2020)
We carried out a simulation of wear in elastic tangential contact in partial-slip mode using the method of dimensionality reduction. The obtained numerical dependencies of wear rate on the number of loading cycles were approximated with existing analytical dependencies, at that, the estimated values of parameters of approximating equations are close to analytical estimates given before. The present results demonstrate the possibility of application of the method of dimensionality reduction to theoretical study of fretting wear rate evolution.